2017
DOI: 10.1002/leap.1095
|View full text |Cite
|
Sign up to set email alerts
|

Openness of Spanish scholarly journals as measured by access and rights

Abstract: Metrics on open access (OA) availability of content published in scholarly journals (i.e. content licences, copyright ownership, and publisher‐stipulated self‐archiving permissions) are still scarce. This study implements the four core variables of the recently published Open Access Spectrum (OAS) (reader rights, reuse rights, copyright, and author posting rights) to measure the level of openness in all 1,728 Spanish scholarly journals listed in the Spanish national DULCINEA database at the end of 2015. Data e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Regarding relevant studies related to Spain, there are articles analysing open access editorial practices (Melero et al, 2017)…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding relevant studies related to Spain, there are articles analysing open access editorial practices (Melero et al, 2017)…”
Section: Key Pointsmentioning
confidence: 99%
“…Regarding relevant studies related to Spain, there are articles analysing open access editorial practices (Melero et al, 2017), perceptions towards open access (Ruiz‐Pérez & Delgado‐López‐Cózar, 2017), to open access and peer review (Segado‐Boj et al, 2018), towards open science (Rodríguez‐Bravo & Nicholas, 2021), and recently with a focus on philosophy (Feenstra & López‐Cózar, 2022) and drivers and barriers in the transition to open science (González‐Teruel et al, 2022). The aim of this paper is to examine and analyse perceptions and editorial practices related to open access, preprints, underlying data and open peer review, from the perspective of editors of scientific journals published in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…In the first, conducted on 1005 journals indexed in Scopus belonging to different disciplines and using all six spectrum variables, no journal obtained a 100% score [26]. In the case of Spanish scholarly journals, a study using the same approach as in this study, applying only the first four variables of the spectrum, found that, in contrast with SciELO, health sciences journals obtained the lowest openness scores [27]. This was because many Spanish biomedical journals are published by commercial publishers, and their content is accessed mainly by subscription, which significantly affects the reader rights component.…”
Section: Resultsmentioning
confidence: 99%
“…Aldaketa-garaiotan aldizkarien irekiera-maila eta egile-eskubideen eta lizentzien erabilera ez da ezagutzen euskal aldizkarien kasuan, inguruko hizkuntzetan luze eta zabal aztertu den gaia den arren (Melero, Laakso, eta Navas-Fernández 2017), eta argitaletxeen politikak jasotzeko propio sortutako datu-baseak ere badaude: Dulcinea 6 eta Sherpa/Romeo 7 . 6.…”
Section: Notesunclassified